Fatigue behaviour of sugar palm fibre reinforced polylactic acid composites for automotive application - Siregar, J. P. (2020)
The heavy consumption of petroleum-based plastics will give a serious impact to environment. Thus, bio-plastics attain attention of researcher in development and design of environmentally friendly composites materials which are possible to replace the petroleum-based plastics. The disposal of the synthetic fibre composites at the end of their lifetime usually need more energy to discharge and large amount of carbon dioxide will be released and causes global warming. Therefore, researchers try to escalate activities in the development and design of environmental friendly composites materials. As a result, natural fibres was used as reinforcement material which to strengthening in polymer matrices. In the other hand, mechanical properties of the natural fibres reinforced thermoplastics polymer composites are very important in order to identify the application of the composites in real life situation. The purpose of this study is to determine the tensile, flexural and impact properties of untreated sugar palm fibre reinforced polylactic acid composites by using different weight percentage (wt. %) of sugar palm to reinforced polylactic acid was 10%, 20% and 30%. A pure polylactic acid was fabricated to use as a reference to be compared with the others three types of specimen. In this study, a new process was used which is vacuum oven was used to melt the pellet of composites then the composites was take out and press it manually using load of 5KN. The tensile testing would follow the standard of ASTM D-638-02a while the flexural test is test using the standard of ASTM-D790. Besides, the impact test is according to the ASTM standard D256. The mechanical properties of all 100% of polylactic acid is the highest compare to 10%, 20% and 30% of sugar palm fibre reinforced with 90%, 80% and 70% of polylactic acid. In all mechanical test, 100% of PLA has the highest strength for tensile, flexural and impact test. The 30% of sugar palm fibre reinforced with 70% polylactic acid composites have lowest tensile and flexural strength but it has higher impact strength compare to 10% and 20% of sugar palm fibre reinforced with 90% and 80% of polylactic acid composites while the impact result shows that there are no influence as the fibre content increase. As conclusion, as the fibre content increases the mechanical properties decreases.